How beekeeping can help farmers adapt to climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In the Nyando basin in Western Kenya, climate change and variability are already evident. Droughts, floods and unpredictable rainfall have increased, affecting agriculture and food security. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa is working with partners in Western Kenya to test a portfolio of interventions that will help farmers to address climate risks and food insecurity. Through a participatory process, beekeeping was identified by women farmers as an option for livelihood diversification. Learn more: www.ccafs.cgiar.org Read more about - Empowering a local community to address climate risks and food insecurity in Lower Nyando, Kenya - http://cgspace.cgiar.org/handle/10568/27889